Navigating containment challenges: A quantitative study of Ghanaian SME performance during the COVID-19 pandemic; Explorando las dificultados ocasionadas por las medidas de contención: Estudio cuantitativo del rendimiento de las PYME ghanesas durante la pandemia de COVID-19 - Karikari Amoa-Gyarteng; Shepherd Dhliwayo; Victoria Adekomaya (Small Business International Review, 2023)
This study aims to provide valuable insights into the containment challenges faced by Ghanaian SMEs during the COVID-19 pandemic and how these challenges impacted key performance indicators (KPIs). Utilizing the partial least square approach of structural equation modelling (PLS-SEM), data collected from a sample of 152 Ghanaian SMEs are examined. The findings underscore the adverse influence of pandemic-related containment measures on financial performance, sales performance, employee satisfaction, and customer satisfaction, while revealing an increase in online engagement as SMEs adapted their business models. Thus, this study highlights the significance of bolstering dynamic capabilities, with a particular focus on digital transformation and leveraging online platforms, as a means to enhance resilience and adaptability for SMEs amidst challenging containment conditions. Theoretical implications emphasize the crucial role of dynamic capabilities in navigating uncertainty and volatility during crises, while the practical implications offer valuable guidance for small business owners in developing economies as they strive to mitigate the impacts of containment measures during public health emergencies on their businesses
Keywords: L26; 330; SME Performance; Dynamic capabilities; COVID-19 containment measures